Standarisasi Simplisia Daun Hantap (Sterculia coccinea Jack) Asal Kabupaten Donggala Propinsi Sulawesi Tengah Sebagai Bahan Baku Sediaan Fitofarmaka - Nurmaya Effendi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2012)
DOWNLOAD PDFStandarization simplisia leaf hantap (Sterculia coccinea Jack) origin Dongala regency of Central Sulawesi Province raw materials preparations for phitopharmaca. The morphological examination showed that hantap leaf plants including dicotyledoneae class with woody stems and roots heels. Transverse slices of the anatomy of the leaf stomata indicate anomositik type, sliced crosswise rod carrier file types are radial. Physical determination powders include determining the total wash content 9.74%, wash content the water soluble and 5.21% wash content that does not dissolve in acid 3.62%. Determination of levels of leaf extract hantap covering levels of water soluble extract, which is 18.89% and levels of ethanol-soluble extract: 14.17%. Identification with chemical reagents contain tannins, steroids and alkaloids. Thin-layer chromatography profiles obtained by the number of spots with more in n-butanol extract with polar eluen chloroform : methanol (20:1) diethyl ether extract compared with non eluen polar heksan: ethyl acetate (8:2). Key words : Standaritation, leaf hantap, tanin, alkaloids, steroids.